PENINGKATAN PENGARUH KINERJA KEUANGAN TERHADAP DINAMIKA HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI PADA BANK UMUM DI INDONESIA - Hakiki, Moh. Saiful; Putra, Riyan Sisiawan; Arifin, Andi Harmoko; Safitri, Julia; Wibowo, Martino (Media Mahardhika, 2024)
This research aims to analyze the relationship between commercial bank financial performance, share price dynamics, and the role of profitability as a moderating variable. Data from 47 commercial banks (conventional and sharia) in Indonesia during the period from the first quarter of 2021 to the third quarter of 2023 was used to test the hypothesis. Independent variables include Net Interest Margin (NIM) and Operational Costs compared to Operating Income (BOPO), while the dependent variable is share price dynamics. Profitability, measured through Return On Assets (ROA) and Return On Equity (ROE), is implemented as a moderating variable. The results of the moderated multiple regression analysis show that financial performance does not directly have a significant influence on stock prices. On the other hand, profitability directly has a positive effect on stock prices. Furthermore, profitability strengthens the relationship between financial performance and share prices, indicating that banks with high profitability tend to experience a more significant impact of financial performance on share price changes. Although it only explains 13.4% of share price variability, these findings provide an in-depth understanding of the factors influencing share price dynamics in the banking sector.